Properties and processability of high ammonia latices - Gorton A D T; Pendle T D (Journal of Natural Rubber Research, 1986)
A systematic study of the physical and chemical properties of samples of mature commercial natural rubber latex concentrate of the high ammonia variety has been carried out. More than forty parameters were measured on each of twenty latices, enabling the current range of variation in each property to be assessed. In many respects the latices were found to be relatively consistent but signiicantly greater variability was found in their response to the addition of zinc ammine ions. This variability is considered to relate to the variable processing behaviour sometimes observed in the user factories. The results obtained in this study did not reveal any strong relationship of zinc ion sensitivity to any other measured property. It appears, therefore, that sensitivity to zinc ions of high ammonia latex is is determined by a combination of several factors the nature of which remains to be determined.